Аманкелді ауданының тарихи топонимикасының кейбір мәселелері - Калиев, Д.Д. (My University, 2013)
This article is sanctified to some problems of historical toponymy of the Amangeldy’s district. Forming of the names of settlements of the Amangeldy’s district in a soviet period. The study of toponymy presents large interest for historical science. These names are envisaged after people resident on this territory, and in spite of different changes, these names contain information about tribes and people of inhabiting these earth. Every region is famous the historical personalities. Amangeldy - in different historical epochs was famous the figures. Therefore the study of history and toponymy of the Amangeldy’s district causes wide interest in scientific circles.